2012
DOI: 10.1021/jp302102k
|View full text |Cite
|
Sign up to set email alerts
|

Drying Transition of Water Confined between Hydrophobic Pillars

Abstract: The phase behavior of the water confined between hydrophobic pillars was studied by using a simple thermodynamic theory and the lattice gas Monte Carlo simulation. The drying transition of water with decreasing spacing between pillars is related to the Wenzel (WZ) to Cassie−Baxter (CB) transition of droplet. Our theory agrees with simulation for pillars with heights ranging from 11 to 100 nm. The present theory further predicts that sufficiently large circular pillars cannot sustain a CB state even if the pill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Previous studies suggested that when two contiguous hydrophobic surfaces are separated, they are connected through a gas bridge. The interfacial free energy of a hydrophobic surface is lower against gas than against water, so it is energetically favorable to replace water with gas between the hydrophobic surface [ 34 ]. A bright “path” appeared in the solution of both MSN and DESN under laser irradiation, while it was not observed in the solution of H-MSN.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that when two contiguous hydrophobic surfaces are separated, they are connected through a gas bridge. The interfacial free energy of a hydrophobic surface is lower against gas than against water, so it is energetically favorable to replace water with gas between the hydrophobic surface [ 34 ]. A bright “path” appeared in the solution of both MSN and DESN under laser irradiation, while it was not observed in the solution of H-MSN.…”
Section: Resultsmentioning
confidence: 99%
“…With increasing W , the liquid confined between the cylindrical or ellipsoidal pillars at S = 0 should increase in both volume and contact area with pillar walls. It turns out that the increase in the volume is faster than the increase in surface area . Consequently, the cohesion of liquid (which scales with volume) dominates over the hydrophobic surface (liquid–pillar interface) effect.…”
Section: Theorymentioning
confidence: 99%
“…The theory was compared with Monte Carlo and molecular dynamics simulations and shown to agree. Owing to the limited sizes of the molecular simulations, however, the previous applications of the theory were limited to nanoscale pillars.…”
Section: Introductionmentioning
confidence: 99%
“…Using theory and Monte Carlo (MC) simulation, we previously studied the CB-to-WZ transition for the surfaces covered with rectangular, cylindrical, and parabolic pillars. 9,10 Interestingly, with increasing S or P, the water droplet penetrated down into the gap between parabolic pillars smoothly from the top to the bottom of the pillars. 10 This contrasts with the abrupt penetration (at a critical value of S or P) into the gap between rectangular or cylindrical pillars, which is characteristic of a first-order phase transition.…”
mentioning
confidence: 99%
“…A detailed description of the present LGMC simulation can be found in our previous work. [9][10][11] Plotted in Figure 1(c) is the average density < ρ > of the water confined between the parabolic pillar walls as a function of S. Regardless of the aspect ratio H/W of the pillar (ranging from 2 to 10), the density smoothly increased from a near-zero value (vapor phase) to a value close to 1 (liquid phase) as S increased from 0.7 to 8.9 nm. This smooth increase in the density is distinctly different from the step-like jump at a critical value of S found for the gap between the rectangular or cylindrical pillar walls.…”
mentioning
confidence: 99%